Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5535/arm.19096
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke Aphasia as a Prognostic Factor for Cognitive and Functional Changes in Patients With Stroke: Ischemic Versus Hemorrhagic

Abstract: Objective To investigate the comprehensive outcomes in aphasic patients, including their cognitive and functional status after ischemic or hemorrhagic stroke. It also aimed to clarify whether aphasia is a prognostic factor for cognitive and functional improvements in stroke patients.Methods Sixty-seven ischemic or hemorrhagic stroke patients in the subacute stage who had been diagnosed with aphasia using the Korean version of Frenchay Aphasia Screening Test (K-FAST) were included in the study. Forty-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…In the final study, significant differences were found between the groups only in the SAS arm control and SAS hand function scores. Different results were reported by Seo et al, where the BI scores were significantly lower in aphasic patients than in non-aphasic controls [ 10 ]. Significantly worse results were found for the group of patients with aphasia, concerning everyday activities (measured with the Functional Independence Measurement), in studies by other authors, both at baseline and at the end of the study [ 12 , 19 ].…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…In the final study, significant differences were found between the groups only in the SAS arm control and SAS hand function scores. Different results were reported by Seo et al, where the BI scores were significantly lower in aphasic patients than in non-aphasic controls [ 10 ]. Significantly worse results were found for the group of patients with aphasia, concerning everyday activities (measured with the Functional Independence Measurement), in studies by other authors, both at baseline and at the end of the study [ 12 , 19 ].…”
Section: Discussioncontrasting
confidence: 60%
“…These include age, type of stroke, presence of cognitive impairments and post-stroke depression, acceptance of the disease, level of self-sufficiency, functional status at admission to a rehabilitation ward, motor function and trunk movements [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The presence of aphasia is also relevant [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the mBI scale does not directly measure communication components, it is noticeable the importance of communication levels on functional recovery. In the literature, the role of communication limitations, such as aphasia, is controversial [ 48 , 49 ]. Like other measures of disability, SDC does not explain the specifics of the disorders (aphasia, apraxia, dysarthria, dementia, deafness) which, individually or in combination, can impair communication.…”
Section: Discussionmentioning
confidence: 99%
“…Although most common screening tools require verbal communication, there are several questionnaires that omit language tasks and may be adapted for patients with aphasia 16,66 . Post‐stroke aphasia is a common consequence of brain injury, diagnosed in approximately one third of acute stroke patients 67 predisposed to post‐stroke cognitive deficits, especially in memory, executive function and attention 68,69 . Therefore, despite diagnostic difficulties, assessment of cognitive function should be an important part of neuropsychological examination of stroke survivors with aphasia.…”
Section: Screening and Diagnosismentioning
confidence: 99%